From Host Defense to Metabolic Signatures: Unveiling the Role of γδ T Cells in Bacterial Infections - Namya Nanda; Martin P. Alphonse (Biomolecules, 2024)
The growth of antibiotic-resistant bacterial infections necessitates focusing on host-derived immunotherapies. γδ T cells are an unconventional T cell subset, making up a relatively small portion of healthy circulating lymphocytes but a substantially increased proportion in mucosal and epithelial tissues. γδ T cells are activated and expanded in response to bacterial infection, having the capability to produce proinflammatory cytokines to recruit neutrophils and clear infection. They also play a significant role in dampening immune response to control inflammation and protecting the host against secondary challenge, making them promising targets when developing immunotherapy. Importantly, γδ T cells have differential metabolic states influencing their cytokine profile and subsequent inflammatory capacity. Though these differential metabolic states have not been well studied or reviewed in the context of bacterial infection, they are critical in understanding the mechanistic underpinnings of the host’s innate immune response. Therefore, this review will focus on the context-specific host defense conferred by γδ T cells during infection with Staphylococcus aureus, Streptococcus pneumoniae, Listeria monocytogenes, and Mycobacterium tuberculosis.